Association between illness perception and health behaviour among stroke patients: The mediation effect of coping style. (22nd January 2021) - Liu, Yanjin; Wei, Miao; Guo, Lina; Guo, Yuanli; Zhu, Yiru; He, Yv
Abstract: Aims: This study aims to explore illness perception and coping style in relation to health behaviour and the mediating role of coping style between illness perception and health behaviour among stroke patients. Design: Cross‐sectional study. Methods: This survey was conducted with 515 stroke patients aged ≥18 years from September 2019 to January 2020 in Zhengzhou, China. The demographic and clinical characteristics questionnaire, Stroke Illness Perception Questionnaire‐Revised, Simplified Coping Style Questionnaire, and Health Behavior Scale for Stroke Patients were included in this study. Data analysis was performed by correlation analysis, multiple linear regression analysis, and structural equation modelling. Results: The valid questionnaires were 495 (effective response rate: 96.1%). Low negative illness perception, high positive coping style, and low negative coping style are related to high level of health promoting behaviour (all p  < 0.01). The results revealed that the effect of illness perception on health behaviour was partly mediated by coping style. It also confirmed that the mediation effect accounts for 43.7% (−0.169/−0.387) of the total effect. Conclusion: Illness perception may influence health behaviour partly because of coping style. Impact: This study implies that targeted interventions for stroke patients' illness perception are needed to motivate them to take proactive coping strategy to ultimately improve their health behaviours.